Kepemimpinan Kepala Desa dalam Penyelenggaraan Pelayanan Publik di Desa Kolam Kecamatan Percut Sei Tuan - Ayu Novidaniati Rusnita; Sulastri Krisdayanti Sinambela; Muhammad Rifai; Julia Ivanna (Universitas Islam Darul Ulum Lamongan, 2024)
This research aims to examine the leadership role of the Village Head in providing public services in Kolam Village, Percut Sei Tuan District. Analysis was carried out on the current condition of leadership which was considered not good by residents, especially regarding the policy of providing unequal aid. During the previous leadership period, aid was given equally to all levels of society, but after the change in leadership, aid tended to be given only to the young. The impact of this policy is citizens' dissatisfaction with leadership which is considered unresponsive and inclusive of the needs of all levels of society. In-depth evaluation of leadership practices is needed to formulate more inclusive and just policies. Leadership that is fair, equitable and pays attention to community diversity is expected to increase citizen satisfaction and collective prosperity. Concrete and sustainable improvement steps are needed to create better and more equitable public services for all Pool Village residents.